The FRB 20121102A November rain in 2018 observed with the Arecibo Telescope. Issue 1 (25th November 2022) - Jahns, J N; Spitler, L G; Nimmo, K; Hewitt, D M; Snelders, M P; Seymour, A; Hessels, J W T; Gourdji, K; Michilli, D; Hilmarsson, G H
ABSTRACT: We present 849 new bursts from FRB 20121102A detected with the 305-m Arecibo Telescope. Observations were conducted as part of our regular campaign to monitor activity and evolution of burst properties. The 10 reported observations were carried out between 1150 and 1730 MHz and fall in the active period around 2018 November. All bursts were dedispersed at the same dispersion measure and are consistent with a single value of (562.4 ± 0.1) pc cm^-3 . The rate varies between 0 bursts and 218 ± 16 bursts per hour, the highest rate observed to date. The times between consecutive bursts show a bimodal distribution. We find that a Poisson process with varying rate best describes arrival times with separations 0.1 s . Clustering on time-scales of 22 ms reflects a characteristic time-scale of the source and possibly the emission mechanism. We analyse the spectro-temporal structure of the bursts by fitting 2D Gaussians with a temporal drift to each sub-burst in the dynamic spectra. We find a linear relationship between the sub-burst's drift and its duration. At the same time, the drifts are consistent with coming from the sad-trombone effect. This has not been predicted by current models. The energy distribution shows an excess of high-energy bursts and is insufficiently modelled by a single power law even within single observations. We find long-term changes in the energy distribution, the average spectrum, and the sad-trombone drift, compared to earlier and later published observations. Despite the large burst rate, we find no strict short-term periodicity.